Analysis of the Legal Certainty of the Issuance of Building Rights Certificates on Sea Areas Based on Government Regulation Number 18 of 2021 - Dina, Lola Ledy Melia; Fikri, Sultoni (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study discusses the issue of legal certainty regarding the issuance of Building Use Rights (HGB) certificates over maritime areas, which has become a legal controversy in Indonesia. The background of this study is the emergence of conflicting interpretations between the agrarian law system, which strictly limits the object of HGB to land, and the increasing practice of granting HGB over sea areas, as illustrated by the case of HGB issuance in the waters of Sidoarjo Regency. The purpose of this research is to analyze the validity and legal certainty of issuing HGB certificates in maritime areas from the perspective of Government Regulation No. 18 of 2021 (PP 18/2021). Using a normative legal research method with a statutory and conceptual approach, this study examines the formal and material legality of HGB issuance based on existing legal norms. The discussion focuses on the discrepancy between the definition of “land” in agrarian law and the classification of “sea” in maritime law, which are governed by different legal regimes. The findings of the study indicate that sea areas, which are part of public spaces regulated Under maritime law, cannot legally be granted HGB unless they have undergone a reclamation process and have been formally designated as state land through administrative procedures. The issuance of HGB over unreclaimed maritime areas leads to administrative defects, violates the principle of legal certainty, and risks harming public interests, particularly the rights of coastal communities. The study concludes that the practice of issuing HGB in maritime areas is legally invalid and recommends regulatory harmonization and strict law enforcement to prevent similar legal violations and to ensure justice and certainty in Indonesia’s land administration system.